Properties of the Escherichia coli DNA Binding (Unwinding) Protein: Interaction with DNA Polymerase and DNA - Molineux, Ian J. (1974)
The E. coli DNA binding protein reduces the activity of the single-strand-specific nucleases associated with all three DNA polymerases known in E. coli. A slight excess of binding protein over that required to saturate the DNA template leads to total inhibition of activity of the 3′ → 5′ nucleases associated with DNA polymerases I and III, but restores maximum activity of the DNA polymerase II-associated nuclease. The binding protein forms a specific complex with DNA polymerase II in the absence of DNA, and it is this complex that degrades a DNA·binding protein complex. Binding protein also facilitates the binding of DNA polymerase II to single-stranded DNA, whereas the binding to DNA of DNA polymerase I is inhibited. These data may explain the specificity with which the binding protein enhances the synthetic ability of DNA polymerase II.